2022
DOI: 10.3390/foods11172661
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Solvent-Assisted Extraction for Recovery of Lipophilic Phytochemicals in Sugarcane Straw and Bagasse

Abstract: Sugarcane is primarily harvested to meet up to 80% of global sugar demand. Recently, lipids recovered from their biomass (straw and bagasse) have attracted much attention due to their possible utilisation in biofuel production but also by the presence of health-promoting compounds as phytosterols (i.e., improvement of cardiovascular function) or 1-octacosanol (i.e., anti-obesity). Although this fraction is commonly obtained through solid–liquid isolation, there is scarce information about how different solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…High-Performance Liquid Chromatography-Evaporative Light Scattering Detection (HPLC-ELSD). The samples were prepared to a concentration of 3 mg/mL in DCM and afterward analyzed on an HPLC (Model 1260 Infinity II; Agilent Technologies, 23 with some modifications described by Teixeira et al 18 The flow rate was set at 0.275 mL/min with an injection volume of 20 μL and the detector evaporator and nebulizer temperature was set at 60 °C with nitrogen as the nebulizing gas at a 1.20 SLM flow rate. In all performed analyses, all of the samples were injected at least in triplicate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-Performance Liquid Chromatography-Evaporative Light Scattering Detection (HPLC-ELSD). The samples were prepared to a concentration of 3 mg/mL in DCM and afterward analyzed on an HPLC (Model 1260 Infinity II; Agilent Technologies, 23 with some modifications described by Teixeira et al 18 The flow rate was set at 0.275 mL/min with an injection volume of 20 μL and the detector evaporator and nebulizer temperature was set at 60 °C with nitrogen as the nebulizing gas at a 1.20 SLM flow rate. In all performed analyses, all of the samples were injected at least in triplicate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The derivatized samples were analyzed on a GC–MS model EVOQ (Bruker, Karlsruhe, Germany) coupled to a mass spectrometer, with a Rxi-5Sil MS column (30 m × 250 μm × 0.25 μm) at a constant flow of 1 mL/min. The carrier gas used was helium, and the GC–MS conditions were as described by Teixeira et al 18 The injector temperature was set at 330 °C with a split of 10, and the oven temperature started at 60 °C with a hold for 5 min, increasing at a rate of 3 °C/min until 330 °C and maintained for 20 min. The MS detector was operated in electron ionization (EI) mode at 70 eV, a source temperature of 280 °C, a transfer line at 300 °C, and a quadrupole in a scan range from 33 to 1000 amu per second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the obtained sugarcane byproduct extract was studied with gas chromatography-mass spectrometry (GC-MS model EVOQ; Bruker, Karlsruhe, Germany) analysis following the methodology described by Teixeira et al [22], which includes a derivatization with N, O-Bis(trimethylsilyl) trifluoroacetamide with 1% trimethylchlorosilane. The equipment used included a GC-QqQ model EVOQ (Bruker, Karlsruhe, Germany) mass spectrometer, with a Rxi-5Sil MS column (30 m × 250 m × 0.25 m nominal).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Teixeira et al [22] showed that sugarcane straw and bagasse have the same group of phytochemicals, namely free fatty acids, hydrocarbons, fatty alcohols, sterols, and phenolic compounds. In this study, several chemical classes of alcohols, free fatty acids, fatty alcohols, phytosterols, hydrocarbons, organic acids, fats, sterols, sugars, and fatty aldehydes were detected in a total of 30 compounds identified.…”
Section: Composition Of the Sugarcane Byproduct Extract (Gc-ms)mentioning
confidence: 99%